Regulation of synthesis of hepatic fatty acid synthetase: binding of fatty acid synthetase antibodies to polysomes. - Alberts, A W (1975)
Mammalian fatty acid synthetase was shown to be composed of two peptides, molecular weight 240,000, after dissociation with sodium dodecyl sulfate. Rat liver polysomes that synthesize fatty acid synthetase were identified by sucrose gradient analysis of polysomes that had been reacted with 125I-labeled antibody against fatty acid synthetase. The binding of 125I-labeled antibody to polysomes was found to correlate with the rate of hepatic fatty acid synthesis in various nutritional conditions.